The Quaternary History of Banks Island, N.W.T., Canada - Vincent, Jean-Serge (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1982)
ABSTRACTBanks Island is a polar desert where continental ice sheets, spreading from a dispersal centre to the southeast, reached their maximum extent on at least three occasions. The oldest Banks Glaciation affected all but the northwest. The Pre-Banks Sea preceded glacierization while the Post-Banks Sea formed during déglaciation. Following Morgan Bluffs Interglaciation, characterized by a climate similar to that of today, the south, the east, and the Thomsen River basin were covered during Thomsen Glaciation. The Pre-Thomsen Sea preceded the glacierization, while the Big Sea inundated much of the Island during déglaciation. Following the last or Cape Collinson Interglaciation, characterized by a climate warmer than that of the hypsithermal, Laurentide glacial lobes impinged on the coastal areas, during the M'Clure Stade of Amundsen Glaciation. Prince of Wales and Thesiger lobes, emanating from Amundsen Gulf, respectively advanced in Prince of Wales Strait and Thesiger Bay impinging on the east and southwest coasts. At the same time, Prince Alfred Lobe, originating in Viscount Melville Sound, advanced in M'Clure Strait and impinged on the north coast. The Pre-Amundsen Sea preceded the glacierization of the south coast, while the East Coast Sea submerged the east coast up to 120 m, the Meek Point Sea the west up to 20 m and the Investigator Sea the north up to 30 m, during déglaciation. The late Sand Hills Readvance of Thesiger Lobe built a morainic system on the southwest coast. Later, the northeast was covered, during the Russell Stade of Amundsen Glaciation, by Viscount Melville Lobe, emanating from Viscount Melville Sound, and the east coast was drowned up to 25 m by the Schuyter Point Sea. Limits of extent of Laurentide ice in the southwestern Archipelago are proposed for the two stades of the last or Wisconsinan Glaciation.